DEVELOPMENT OF OLIGOMERIC ANTIPYREN FOR POLYMERIC BUILDING MATERIALS (Academicia Globe: Inderscience Research, 2021)
The article presents the result of the preparation of oligomeric flame retardants based on the products of the interaction of phosphorus -boron-containing compounds of the grades Aj-4,Aj-5, Aj-6 and also studied the fire retardant efficiency of treated wooden samples providing the 1st group of fire- retardant efficiency , according to GOST 16363-98